Antipsychotic Treatment Reduces Indices of Oxidative Stress in First-Episode Psychosis Patients. (27th July 2016) - Kriisa, Kärt; Haring, Liina; Vasar, Eero; Koido, Kati; Janno, Sven; Vasar, Veiko; Zilmer, Kersti; Zilmer, Mihkel
Abstract : 38 first-episode psychosis (FEP) patients and 37 control subjects were recruited for the study of indices of oxidative stress (OxS). The main purpose of the study was to compare the OxS statuses (serum total antioxidant capacity (TAC), total level of peroxides (TPX), oxidative stress index (OSI), and ratio oxidized methionine (Met-SO) to methionine (Met)) between antipsychotic-naïve FEP patients and individuals without a history of psychiatric disorders. Subsequently, the impact of 7-month antipsychotic treatment was evaluated on the OxS status in FEP patients. An attempt was made to assess links between OxS signature and inflammation markers. The oxidative stress indices remained generally unchanged in antipsychotic-naïve FEP patients compared to control subjects. Despite that, there was a significant correlation between the levels of TPX and EGF (endothelial growth factor) in FEP patients. This correlation disappeared after antipsychotic treatment of FEP patients. Moreover, antipsychotic treatment was associated with a significant reduction in OxS indices, including TPX, OSI, and ratio between Met-SO and Met. By contrast, in chronic SCZ patients we established a significant high-grade OxS. In conclusion, the markers of total antioxidative capacity, lipid peroxidation, and protein oxidation revealed no high-grade OxS in FEP patients. Nevertheless, antipsychotic treatment induced a considerable anti-inflammatory effect. OxS levels were also significantly decreased if compared in FEP patients before and after antipsychotic treatment.